Genomic stability in response to high versus low linear energy transfer radiation in Arabidopsis thaliana - Huefner, Neil D.; Yoshiyama, Kaoru; Friesner, Joanna D.; Conklin, Phillip A.; Britt, Anne B. (Frontiers in Plant Science, 2014)
Low linear energy transfer (LET) gamma rays and high LET HZE (high atomic weight, high energy) particles act as powerful mutagens in both plants and animals. DNA damage generated by HZE particles is more densely clustered than that generated by gamma rays. To understand the genetic requirements for resistance to high vs. low LET radiation, a series of Arabidopsis thaliana mutants were exposed to either 1GeV Fe nuclei or gamma radiation. A comparison of effects on the germination and subsequent growth of seedlings led us to conclude that the relative biological effectiveness (RBE) of the two types of radiation (HZE vs. gamma) are roughly 3:1. Similarly, in wild-type lines, loss of somatic heterozygosity was induced at an RBE of about a 2:1 (HZE vs. gamma). Checkpoint and repair defects, as expected, enhanced sensitivity to both agents. The "replication fork" checkpoint, governed by ATR, played a slightly more important role in resistance to HZE-induced mutagenesis than in resistance to gamma induced mutagenesis.